Prediction of Post-operative Visual Deterioration Using Visual-Evoked Potential Latency in Extended Endoscopic Endonasal Resection of Craniopharyngiomas - Tao, Xiaorong; Yang, Xiaocui; Fan, Xing; You, Hao; Jin, Yanwen; Liu, Jiajia; Guo, Dongze; Li, Chuzhong; Qiao, Hui (Frontiers in Neurology, 2021)
Background The current study aimed to investigate the predictive value of visual evoked potential (VEP) latency for postoperative visual deterioration in patients undergoing craniopharyngioma resection via extended endoscopic endonasal approach (EEEA). Methods Data from 90 patients who underwent craniopharyngioma resection via EEEA with intraoperative VEP monitoring were retrospectively reviewed. P100 latency was compared between patients with and without postoperative visual deterioration, and the threshold value of P100 latency for predicting postoperative visual deterioration was calculated by the Receiver operating characteristic (ROC) curve analysis. In addition, other potential prognostic factors regarding postoperative visual outcomes were also analyzed by multivariate analysis. Results Patients with postoperative visual deterioration showed a significantly longer VEP latency than those without (p<0.001). An extension over 8. 61% in VEP latency was identified as a predictor of postoperative visual deterioration (p<0.001). By contrast, longer preoperative visual impairment duration and larger tumor volume were not significant predictors for postoperative visual deterioration. Conclusions The current study revealed that intraoperative VEP monitoring in EEEA is effective for predicting postoperative visual deterioration, and an extension over 8. 61% in VEP latency can be used as a critical cut-off value to predict postoperative visual deterioration.